Iowa RBA, December 25, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for December 25, 1995. Highlights of the update include sightings of Common Redpoll, Hoary Redpoll, Barrow's Goldeneye, Glaucous Gull, Townsend's Solitaire and Red Crossbill. Birds sighted includes species from some Christmas counts. Also included are handwritten notes for the next week's update with sightings of two first year Thayer's Gulls and an adult Lesser Black-backed Gull. Epson - sheet feed/flatbed